2006
DOI: 10.1021/es0517320
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 14 Polycyclic Aromatic Hydrocarbons in Mainstream Smoke from U.S. Brand and Non-U.S. Brand Cigarettes

Abstract: Tobacco smoke contains thousands of chemical compounds, including many carcinogenic polycyclic aromatic hydrocarbons (PAHs). To determine the concentration ranges of PAHs in tobacco smoke and to understand what factors alter their levels, we quantitatively measured 14 PAHs in mainstream smoke from a transnational U.S. brand (Marlboro) and from locally popular brand cigarettes from 14 countries. We used standardized machine smoking conditions (35-mL puff volume, 60-s puff interval, and 2-s puff duration), extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 10 publications
8
62
0
2
Order By: Relevance
“…Furthermore, an inverse relationship between the yield of TSNAs and PAH has been consistently observed. For example, Ding et al (2006) reported that PAH were inversely correlated with total carcinogenic TSNAs and nitrate content, confi rming earlier studies which demonstrated that tobacco blend (types of tobacco) and nitrate levels (formed during tobacco combustion) infl uence the mainstream yields of PAH and TSNA ( Adams, Lee, & Hoffmann, 1984 ;Hoffmann & Wynder, 1967 ) .…”
Section: Tobacco-specifi C Nitrosamine Exposures Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, an inverse relationship between the yield of TSNAs and PAH has been consistently observed. For example, Ding et al (2006) reported that PAH were inversely correlated with total carcinogenic TSNAs and nitrate content, confi rming earlier studies which demonstrated that tobacco blend (types of tobacco) and nitrate levels (formed during tobacco combustion) infl uence the mainstream yields of PAH and TSNA ( Adams, Lee, & Hoffmann, 1984 ;Hoffmann & Wynder, 1967 ) .…”
Section: Tobacco-specifi C Nitrosamine Exposures Discussionsupporting
confidence: 64%
“…They have been identifi ed in cigarette tobacco ( Ashley et al, 2003 ;Brunnemann, Cox, & Hoffmann, 1992 ;Song & Ashley, 1999 ), environmental tobacco smoke (ETS ; Brunnemann et al, 1992 ), smokeless tobacco ( Hoffmann, Adams, Lisk, Fisenne, & Brunnemann, 1987 ), and other tobacco products such as cigars, toombak, and bidi cigarettes ( Idris, Prokopczyk, & Hoffmann, 1994 ;McNeill, Bedi, Islam, Alkhatib, & West, 2006 ;Murphy, Carmella, Idris, & Hoffmann, 1994 ;Nair, Pakhale, & Bhide, 1989 ). Furthermore, TSNA yields in tobacco smoke vary signifi cantly in tested cigarettes from different parts of the world as the formation of TSNAs is infl uenced by the tobacco blend and the curing processes ( Ashley et al, 2003 ;Ding et al, 2006 ).…”
Section: Tobacco-specifi C Nitrosamine Exposures In Smokers and Nonsmmentioning
confidence: 99%
“…In a recent study Gevao and colleagues have established that the estimated human nondietary exposure from dust contributes to 42% of PAH in children and 11% only in adults, and thus the children are at a greater risk in spite that they are not exposed additionally to tobacco smoke or dietary PAH [30]. It is apparent in our study that children living with relatives who smoke at home, or merely staying in the same room with a smoker, are at a considerably higher risk of having elevated serum PAH levels, since it is well established that smoking is a direct contributor to PAH exposure among humans [31][32][33]. While there is little definite evidence that tobacco smoke exposure during childhood is a strong risk factor for liquid chromatography with UV-detection.…”
Section: Discussionmentioning
confidence: 61%
“…Our previous studies on popular commercial cigarettes revealed that both PAH and TSNA yields in tobacco smoke vary significantly in cigarettes from different parts of the world (15). Formation of mainstream smoke PAHs and TSNAs are influenced by the tobacco blend.…”
Section: Introductionmentioning
confidence: 99%